Investigating the relation between removable denture prosthesis and sublingual varices - Naeemi Dadkhahan, Hamidreza; Alaee, Arezoo; Lavaf , Shirin (Researcher Bulletin of Medical Sciences, 2021)
Objective: In this research, the scientific and practical question, whether or not people with sublingual varices were more exposed to dental prosthesis than those who did not have sublingual varices, was answered. Materials and Methods: The case-control study was done by referring to the Kahrizak Alborz charity sanatorium. A list of seniors over 60 years were prepared and referred to each of them after justifying the plan and obtaining their consent were analyzed, sampled. The case group was those who suffered from sublingual varices and the control group were those who did not have sublingual varices and in terms of age, sex, smoking, high blood pressure and leg varice were similar to those of the case. Varices detection was evaluated by clinical examination and according to the standard method. Sublingual varices were examined and recorded based on age, sex, dental prosthesis, smoking, leg varices, blood pressure, literacy level. Exposure level of two groups with denture prosthetics were Judged by the statistics with chi-square test, Fisher exact, and odds ratio. Results: A total of 141 patients with sublingual varices and 141 controls were studied. The subjects were two groups. Exposure to denture in the control group was 65 (46%) and in the case group 100 (71%). Conclusion: It seems that having removable denture prosthesis increases the chance of developing sublingual varices.